Size of sampling units aproppriate for management level forest inventory in Eastern Amazon, Brazil - Sousa, Carla Samara Campelo de; Silva, José Antônio Aleixo da; Ferreira, Rinaldo Luiz Caraciolo; Silva , Diego Armando Silva da; Silva, Evandro Ferreira da; Lima, Robson Borges de (Revista em Agronegócio e Meio Ambiente, 2023)
This study aimed to indicate the ideal sample size for continuous forest inventories in the tropical forest in Amapá. Data were obtained from a monitoring inventory started in 2010 and completed in 2016, in five permanent sampling units of 100m x 100m with an inclusion level of DBH ? 10cm. Randomly allocated sample subunits with five different dimensions ranging from 400 m2 to 1600 m2 were simulated within these units. The measurement times of each sampling unit, from the first to the last three, were timed. Dimensions were analyzed for their accuracy and relative efficiency. Given the above and depending on the purpose of the inventory, the standard sampling unit of 1 ha (100 m x 100 m) is recommended for the inventory variables. The 20 m x 20 m (400 m2) square sampling unit was the most suitable for monitoring growth variables (annual increment in diameter, basal area, and volume), indicating that these sampling units for continuous inventories can become an essential alternative for use in monitoring inventory in the region.